Mentoring physical education teachers in the secondary school : a practical guide - Capel, Susan Anne, 1953-; Lawrence, Julia Clare (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"Mentoring Physical Education Teachers in the Secondary School helps mentors of new Physical Education teachers in both developing their own mentoring skills and providing the essential guidance their trainees need as they navigate the rollercoaster of the first years in the classroom. Offering tried-and-tested strategies based on the best research, it covers the knowledge, skills and understanding every mentor needs and offers practical tools such as lesson plans and feedback guides, observation sheets, and examples of dialogue with trainees" --
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Physical education teachers -- Training of -- Handbooks, manuals, etc; Mentoring in education -- Handbooks, manuals, etc; Physical education teachers -- Education (Secondary) -- Handbooks, manuals, etc; Physical education and training -- Study and teaching (Secondary) -- Handbooks, manuals, etc; Professeurs d'éducation physique -- Formation -- Guides, manuels, etc; Mentorat en éducation -- Guides, manuels, etc; Professeurs d'éducation physique -- Enseignement secondaire -- Guides, manuels, etc; Éducation physique -- Étude et enseignement (Secondaire) -- Guides, manuels, etc; EDUCATION -- Elementary; Mentoring in education; Physical education and training -- Study and teaching (Secondary); Physical education teachers -- Training of; Handbooks and manuals